UMP holds Jalinan Kasih Bersama Komuniti for Baloks Rohingyas - UMP, PNC (2019)
Concerned about the plight of displaced fellow Muslims of Rohingya ethnic from Myanmar, Universiti Malaysia Pahang’s (UMP) Association of Professional & Administrative Officers (PPTI) recently conducted a community programme called ‘Jalinan Kasih Bersama Komuniti’, in collaboration with a number of the university’s strategic partners.